Knowledge and vaccination status of hepatitis B amongst medical interns of Rural Medical College, Loni, Maharashtra, India (South East Asia Journal of Public Health, 2014)
Hepatitis B Virus (HBV) infection is a serious global public health problem. It is the most common blood borne viral infection which places healthcare professional at higher occupational risk. The present study was conducted to assess the current knowledge and vaccination status about hepatitis B amongst medical interns. A cross-sectional study was conducted between February and March 2009 on 100 medical interns of the Rural Medical College, Loni, India. A pre-designed questionnaire which assessed their knowledge of hepatitis B was the tool of data collection. The data was analyzed in the form of percentage and proportions, and the chi-square test was applied. In the present study, 83.3% of interns showed a good level of knowledge regarding hepatitis B infection. The percentage of interns with the correct knowledge regarding post exposure prophylaxis and mode of transmission of hepatitis B were 89% and 90% respectively. It was found that 87% of the respondents espoused vaccination as a measure for the prevention of hepatitis B and 72% of the interns were fully immunized against hepatitis B. However, there is a misconception about prophylaxis, vaccination and the treatment of HBV. Hence there is an imperative need for health education to improve the knowledge of the interns towards hepatitis B infection. DOI: http://dx.doi.org/10.3329/seajph.v3i2.20034 South East Asian Journal of Public Health Vol.3(2) 2013: 19-22